(Analysis of Government Response to Natural Disaster Management in Sumatra: A Case Study on Response Delays, Interagency Coordination, and Institutional Capacity) - Dedeh Maryani; Nindya Adhisty; Sutan Riska Tuanku Kerajaan; Subhandhy Subhandhy; Muhammad Iqbal Sarabayan Pazka (Sean Institute, 2025)
This study employed a qualitative research method, focusing on a case study of the recent flood disasters in Sumatra that occurred over the past two weeks. The research aims to evaluate the government’s response to these disasters through the lens of Mazmanian and Sabatier’s policy implementation theory, which emphasizes three primary determinants of policy implementation success: problem tractability, the ability of policy decisions to structure implementation, and non-statutory variables, including local context, organizational culture, and political support.The findings indicate that delayed initial responses, fragmented coordination among government agencies and technical institutions, and limited institutional capacity significantly undermined the effectiveness of flood management. Furthermore, although existing policy frameworks have been formalized, they remain insufficiently adaptive and do not provide adequate operational mechanisms to address the complex and dynamic nature of disaster events. These shortcomings have contributed to heightened public dissatisfaction and demands from communities struggling for survival. This study is expected to provide academic insights and constructive guidance for the government in enhancing policy implementation for disaster management, particularly in the context of the ongoing floods in Sumatra